2008
DOI: 10.1103/physrevlett.101.177005
|View full text |Cite
|
Sign up to set email alerts
|

K-Doping Dependence of the Fermi Surface of the Iron-ArsenicBa1xKxFe2As2Superconductor Using Angle-Resolved Photoemission Spectrosc

Abstract: We use angle-resolved photoemission spectroscopy (ARPES) to investigate the electronic properties of the newly discovered iron-arsenic superconductor, Ba1−xKxFe2As2 and non-supercondcuting BaFe2As2. Our study indicates that the Fermi surface of the undoped, parent compound BaFe2As2 consists of hole pocket(s) at Γ (0,0) and larger electron pocket(s) at X (1,0), in general agreement with full-potential linearized plane wave (FLAPW) calculations. Upon doping with potassium, the hole pocket expands and the electro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
168
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(189 citation statements)
references
References 21 publications
20
168
1
Order By: Relevance
“…In such an electronic structure, interactions between electrons near the two sets of pockets give rise to a spin density wave (SDW) order at the wave vector connecting them 8 . This itinerant picture is consistent with the wave vector of the observed antiferromagnetism, angle resolved photoemission (ARPES) measurements of the electronic structure 9,10 and the evolution of the dynamic magnetic susceptibility with carrier concentration [11][12][13] .…”
supporting
confidence: 85%
“…In such an electronic structure, interactions between electrons near the two sets of pockets give rise to a spin density wave (SDW) order at the wave vector connecting them 8 . This itinerant picture is consistent with the wave vector of the observed antiferromagnetism, angle resolved photoemission (ARPES) measurements of the electronic structure 9,10 and the evolution of the dynamic magnetic susceptibility with carrier concentration [11][12][13] .…”
supporting
confidence: 85%
“…Presence of 3D Fermi surfaces (FSs) was also suggested from band structure calculations 22 and a number of other experimental probes. [23][24][25][26][27] In particular, recent ab-initio LDA+Gutzwiller calculations, where electron correlations are taken into account beyond LDA, indicated that the large-size 3D ellipsoid like FS has a dominant Fe-3d 3z 2 −r 2 orbital characteristic 22 . Then the key issue is to understand why an s-wave superconducing energy gap is clearly seen from the in-plane optical measurement, whereas a large residual quasiparticle population is indicated in the c-axis polarized optical measurement.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the results obtained reveal that various atomic replacements inside "122" phases can lead to essential anisotropic changes of their structural properties and are favorable for fine tuning of their geometry -in particular, in view of sensitivity of superconductivity to structural changes, see [31,32].…”
Section: Structural Propertiesmentioning
confidence: 91%